2023
DOI: 10.3390/molecules28135277
|View full text |Cite
|
Sign up to set email alerts
|

Protopine Alleviates Dextran Sodium Sulfate-Induced Ulcerative Colitis by Improving Intestinal Barrier Function and Regulating Intestinal Microbiota

Abstract: Ulcerative colitis (UC) is an inflammatory bowel disease (IBD), and its pathogenesis is related to intestinal mucosal barrier damage and gut microbiota imbalance. Protopine (PRO), an isoquinoline alkaloid, is one of the main anti-inflammatory ingredients of traditional Chinese medicine Macleaya cordata (Willd.) R. Br. This study investigated the effects of PRO on the intestinal mucosal barrier and gut microbiota in dextran sodium sulfate (DSS)-induced colitis mice. C57BL/6J mice were treated with 3% DSS in dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, the causal relationship between ulcerative colitis and gut microbiota dysbiosis is still unknown, but it is undeniable that improving the composition of gut microbiota is beneficial for repairing the colonic mucosal barrier and enhancing local and systemic immunity, which has gradually become a new treatment for UC. Our study found that RRTE can inhibit the abundance of pathogenic bacteria such as Staphylococcus [64], Shigella [65], and Enterococcus [45]; at the same time, increase the abundance of Ruminococcus and Turicibacter, which are associated with the production of short-chain fatty acids [66,67], as well as Parabacteroides, which have protective effects in UC and are considered the next generation of probiotics. In addition, LDA analysis results showed that g_Turicibacter is the dominant bacterial group in Group H. Relevant studies have shown that its abundance was negatively correlated with the expression of IL-1β, IL-6, and TNF-α.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, the causal relationship between ulcerative colitis and gut microbiota dysbiosis is still unknown, but it is undeniable that improving the composition of gut microbiota is beneficial for repairing the colonic mucosal barrier and enhancing local and systemic immunity, which has gradually become a new treatment for UC. Our study found that RRTE can inhibit the abundance of pathogenic bacteria such as Staphylococcus [64], Shigella [65], and Enterococcus [45]; at the same time, increase the abundance of Ruminococcus and Turicibacter, which are associated with the production of short-chain fatty acids [66,67], as well as Parabacteroides, which have protective effects in UC and are considered the next generation of probiotics. In addition, LDA analysis results showed that g_Turicibacter is the dominant bacterial group in Group H. Relevant studies have shown that its abundance was negatively correlated with the expression of IL-1β, IL-6, and TNF-α.…”
Section: Discussionmentioning
confidence: 57%
“…The HE results showed that RRTE can protect the normal structure of colon tissue and reduce inflammatory infiltration. The transmembrane protein occludin and mucin MUC1 are important components of the TJs and mucus layer, respectively [44], which together maintain the intestinal mechanical barrier; aberrant expression of these protein expressions can increase intestinal permeability and promotes intestinal inflammation [45]. RRTE can increase the expression of occludin and MUC1, suggesting that RRTE can play a protective role in UC by protecting the intestinal mechanical barrier.…”
Section: Discussionmentioning
confidence: 99%
“…In the pathological state, the hepatic circulatory function is diminished. Excessive LPS stimulates and binds the Toll-like receptor 4 (TLR-4) in Kupffer cells, causing activation of these cells and subsequent activation of the NF-κB pathway for the release of inflammation-associated factors and chemokines, including IL-1β, IL-6, TNF-α, and MCP-1. In this study, we hypothesized that UEP regulated the liver axis by inhibiting the LPS-mediated NF-κB pathway. Meanwhile, UEP reduced LPS translocation to the liver, attenuated hepatocellular necrosis and hepatic macrophage infiltration, and decreased serum AST, ALT, and the expression of IL-1β, IL-6, and TNF-α (see Figure ).…”
Section: Discussionmentioning
confidence: 99%